Factors influencing the adoption of sustainable practices in rice cultivation in Costa Rica - Barrantes-Aguilar, Luz (2024)
Introduction. Sustainable practices are important tools for mitigating and adapting to climate change, making it essential to understand the factors influencing rice producers’ decisions to adopt conservation practices in their production system. Objective. To determine the causal relationships between variables that explain the adoption of conservation practices by rice producers. Materials and methods. A study was conducted between July and September 2021 in rice production systems in Costa Rica, involving producers from the Brunca, Chorotega, Huetar, and Central Pacific regions through quota sampling. A survey was administered to a total of 67 rice producers. The research was quantitative, identifying degrees of adoption of conservation practices, performing cluster groupings, and using an ordered probit model was to analyze the factors influencing the intensity of adoption of conservation technologies or practices in these production systems. Results. Greater adoption of conservation practices in rice production systems was influenced by the producer’s level of education, membership or affiliation with organizations in rice sector, and land ownership. Conclusions. The design of strategies for conservation practice  in rice cultivation benefits from a better understanding of the relationships between socioeconomic, productive, and environmental variables, which can increase the likelihood that a producer will implement and maintain these conservation practices over time.